Nécropoles protohistoriques de la région de Castres (Tarn) Le Causse, Gourjade, Le Martinet - Giraud, Jean-Pierre; Pons, Fabrice; Janin, Thierry (Documents d'archéologie française, 2003)
Between 1987 and 1995, rescue excavations were carried out on three Late Bronze Age / Early Iron Age cremation burial cemeteries in the Castres area of the Tarn region (Gourjade and Le Martinet near Castres, Le Causse at Labruguière). These vast funerary complexes, containing more than 1,200 burials, were considered to form an indivisible whole and as such were listed as sites of national importance in 1995. Study of archaeological finds from the sites, comprised of almost 5,300 vessels and some 1,300 metal objects, has led to developing a simple common typology similar to those defined for cemeteries in the western lower Languedoc region. Typological characteristics are examined in detail and presented in conjunction with distribution maps. A detailed study of funerary architecture and deposit distribution, using the same approach as the spatial analysis, is presented in the following chapter. These observations provide the basis for suggestions concerning the chronological sequencing of the burials. The resulting seriation conclusively demonstrates the presence of five groups, thus shedding light on the evolution of material culture and funerary assemblages in the Castres cemeteries over more than three centuries (from the 9th to the first half of the 6th c BCE) and indicating that significant changes took place during the Bronze Age / Iron Age transition period. The study of topographical evolution points to logical patterns of development which were concentric at Causse and Goujade and linear at Martinet. Anthropological analysis, which is based on a remarkable sample comprised of more than 1,200 bone assemblages, unique in France for this period, has provided information on selection within the cemeteries and on changes in deposits and their constituents. A chapter is also given over to animal remains which are both numerous and varied, particularly at Causse. The study demonstrates changes in both the quantity and the qua lit y of meat offerings over time and provides a pertinent view of this practice. The paleosociological analysis which follows adopts a classical approach in which ail parameters are taken into consideration. The results indicate that deposits are relatively uniform and point to a degree of social levelling within the communities. The final chapter considers the cemeteries cultural identity and their regional connections. Study of available documentation over a wide area, extending from Provence to Aquitaine, demonstrates strong links with Mediterranean groups, primarily those from the western lower Languedoc area. The studies and syntheses are based upon abundant documentary evidence which is presented in its entirety in the second and third volumes.